Exogenous steroid-induced hypoadrenalism in a person living with HIV caused by a drug–drug interaction between cobicistat and intrabursal triamcinolone. Issue 1 (14th December 2018) - Makaram, Navnit; Russell, Clark D; Roberts, Simon Benedict; Stevens, Jarrad; Macpherson, Gavin
Abstract : We report a diagnosis of exogenous steroid-induced hypoadrenalism in a person living with HIV caused by a drug–drug interaction (DDI) between intrabursal triamcinolone and the pharmacokinetic booster cobicistat. A 53-year-old woman living with HIV, managed with dolutegravir and cobicistat-boosted darunavir, presented to the orthopaedic clinic with worsening hip pain. She was diagnosed with greater trochanteric pain syndrome (GTPS) of the hip and was treated with intrabursal injection of bupivacaine and triamcinolone. Seven days following this injection, she presented with Cushingoid features, an undetectable cortisol and was diagnosed with exogenous steroid-induced hypoadrenalism. Cobicistat is a cytochrome P450 3A inhibitor and in this case inhibited clearance of intrabursal triamcinolone, leading to exogenous glucocorticoid excess and adrenal suppression. This is the first report to describe this predictable DDI with cobicistat following intrabursal glucocorticoid injection. This case highlights the complexities in managing non-HIV-related chronic morbidities in people living with HIV.